2014
DOI: 10.1002/ptr.5174
|View full text |Cite
|
Sign up to set email alerts
|

Curcuminoid Treatment for Knee Osteoarthritis: A Randomized Double‐Blind Placebo‐Controlled Trial

Abstract: Treatment of osteoarthritis (OA) is challenging owing to the inefficacy and long-term adverse events of currently available medications including non-steroidal anti-inflammatory drugs. Curcuminoids are polyphenolic phytochemicals with established anti-inflammatory properties and protective effects on chondrocytes. The aim of this study is to investigate the clinical efficacy of curcuminoids in patients suffering from knee OA. A pilot randomized double-blind placebo-control parallel-group clinical trial was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
227
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 251 publications
(241 citation statements)
references
References 48 publications
7
227
0
7
Order By: Relevance
“…37 We also excluded one study because there was no relevant outcome 38 and one (abstract) because it was a duplicate of another excluded study. 39 Finally, we included seven studies [40][41][42][43][44][45][46] with a total of 797 participants. Key details of the included studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…37 We also excluded one study because there was no relevant outcome 38 and one (abstract) because it was a duplicate of another excluded study. 39 Finally, we included seven studies [40][41][42][43][44][45][46] with a total of 797 participants. Key details of the included studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In four studies the proportion of participants with bilateral knee OA ranged from 37% 44 to 100%. 45 Three studies 42,43,46 did not report the proportion of participants with bilateral knee OA. The mean age of the participants ranged from 57 to 69 years, and the duration of intervention was between 4 and 16 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations